The monitoring process of column flotation using ECVT system with the effect of percent solid and frother dosage to recovery - Soesaptri Oediyani; Didied Haryono; Mira Elisabeth; Rahman Faiz Suwandana (Jurnal Teknika, 2023)
Flotation is a separation process that exploits differences in the surface properties of minerals and their impurities when exposed to a solution medium. To effectively observe and monitor the flotation process, Electrical Capacitance Volume Tomography (ECVT) has emerged as a valuable monitoring technology. By employing ECVT, the performance of flotation can be successfully monitored, particularly in relation to the dosage of frother and the percentage of solids. In this study, a laboratory-scale flotation column, equipped with 32 capacitance sensors located in the collection zone section, was employed to facilitate the monitoring process. The measurements of capacitance values were conducted at level 5, which represents the steady-state region of the flotation process. By varying the dosage of frother and the percentage of solids, the study explored the impact of these variables on the flotation performance. The experiments encompassed different solid percentage variations, including 7.5%, 10%, 12.5%, and 15% solid, in conjunction with varying frother dosages of 10, 20, 30, 40, and 50 ppm. The experimental results demonstrated that both the recovery and the signal capacitance exhibited a tendency to increase up to a maximum point as the frother dosage and solid percentage were varied. Notably, the changes in the signal capacitance and recovery displayed a parallel pattern, which was further confirmed through the three-dimensional images obtained using ECVT. These images visually depicted alterations in color concentration in accordance with the variations in frother dosage and solid percentage. The study identified the lowest recovery of 12.34% under the condition of a 10 ppm frother dosage and 12.5% solid, corresponding to a capacitance value of 1.177. Conversely, the highest recovery achieved was 49.91% when using a 40 ppm frother dosage and 15% solid, with a corresponding capacitance value of 1.270.